PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT DENGAN BERBANTUAN MEDIA DADU BERGAMBAR DAN PIRAMIDA KERAGAMAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA GUNA MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD 2 SINGOCANDI - Nurul Imamah; Siti Masfu’ah; Tianida Nilamsari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to improve students' learning outcomes in the cognitive domain in the Pancasila Education subject by implementing the Teams Games Tournament learning model assisted by dice media with pictures and pyramids of diversity in grade III students of SD 2 Singocandi in February 2025 with the material Different is Beautiful. The research method used in this study is classroom action research which is carried out in two cycles, with each cycle consisting of four stages, namely the planning, implementation, observation, and reflection stages. The subjects in this study were 31 grade III students of SD 2 Singocandi consisting of 19 male students and 12 female students. Data collection techniques in this study include interviews, observations, tests, and documentation. Student learning outcomes in the cognitive domain in cycle I increased with an average percentage of 64%, and in cycle II increased with an average percentage of 77%. Based on these results, it can be concluded that the application of the Teams Games Tournament learning model assisted by dice media with pictures and pyramids of diversity can improve the learning outcomes of Pancasila Education in grade III students.